Analysis of dynamic characteristics of CO2 concentration in subway cars - Yang Huagan; Wang Haiying; Wu Yan (E3S Web of Conferences, 2022)
The air environment in the subway car has a great impact on the comfort and health of passengers. In order to know the real air quality in the car when the train is running, this paper takes CO2 as an indicator and conducts a field test on Line 11 of Shanghai Metro to study and analyse the dynamic CO2 concentration and the fresh air rate in the subway car. The results show that the CO2 concentration increases from the head car to the tail car, and the fresh air volume decreases from the head car to the tail car is the reason for the large difference of CO2 concentration in different cars. The CO2 concentration in the car is greatly affected by the passenger load, and the maximum value of CO2 concentration in the morning peak can reach 2.3 times that of the normal hours. The background CO2 concentration has a certain influence on the CO2 concentration in the car, and the CO2 concentration in the underground line is higher than that in the elevated line in the same carriage. The CO2 concentration in subway cars of the underground line in the morning peak is significantly higher than 1500 ppm, which indicates that the dilution effects of the ventilation can’t meet the fresh air requirements in the morning peak. The research in this paper can provide a reference for the design of the ventilation system of subway trains and the environmental control in the car.